(untitled) (Hekima Review, 2023)
Our primary objective in this article is to describe the kind of Church we aspire to be a part of. We envision a Church confronting its challenges with self-awareness, avoiding stagnation and isolation. This Church actively listens to its diverse members, striving for unity and harmony among them. It acknowledges its limitations and remains open to learning from others. An encouraging example of this openness is found in the encyclical Laudato Si, which signals hope for closer alignment between the Church’s beliefs and other fields of knowledge. This article also advocates for a Church that embraces all its members and those who seek to belong to it. It envisions a Church with shared understandings, fostering commitment and collective progress toward a common destiny: God.